Why is it so difficult to recruit patients to research in emergency care? Lessons from the AHEAD study. Issue 1 (31st March 2015) - Johnson, Rowena; Kuczawski, Maxine; Mason, Suzanne
Abstract : Introduction: In February 2014, all 23 National Institute for Health Research medical research specialities were failing to meet recruitment targets, with 'Injuries and Emergencies' research performing particularly poorly. In this paper, the multicentre AHEAD study was used to explore issues surrounding recruitment in UK emergency departments. Method: The AHEAD study investigated management and outcomes in over 3000 anticoagulated patients who suffered a head injury. Data from the study were used to compare patient recruitment at 33 Type-1 emergency departments. A questionnaire was sent to a research nurse at each of these sites and 30 replied (91% response rate). The survey investigated the difficulties encountered during patient recruitment and whether these were related to recruitment methods. More detailed interviews were conducted with three research nurses, to gain further insight into the barriers and facilitators involved. Results: Overall recruitment varied widely between sites with an eightfold variation in recruitment rates. Population demographics and other uncontrollable factors will partly contribute to this variation. However, research nurses reported many problems, including site resources, lack of staff engagement and flaws in recruitment strategies, which could be improved. Conclusions: Many of the barriers to recruiting patients for research studies encountered by research nurses have previously been reported in the literature, but there remain consistent problems. Until solutions are found, researchers will continue to miss recruitment targets and this will have implications for the efficiency and quality of emergency medicine research in the UK.